2021
DOI: 10.30574/gscarr.2021.9.2.0267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irradiation process on mango

Abstract: Mango (Mangifera indica L.) is one of the choicest tropical fruit of the world and rightly designated as "King" of all fruits. It is a nutritionally important fruit being a good source of vitamin A, B and C and minerals. Post-harvest losses in mangoes have been estimated in the range of 25 to 40% from harvesting to consumption stage. Improved practices and preservation have a great impact on retaining mango fruit quality and on the supply chain. Nowadays food irradiation process is an engrained technology for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Notably, many researchers have forced on the inactivating microorganisms and endogenous enzymes for the purpose of fruit food preservation and conservation (Landl et al., 2010; Liu, Grauwet et al., 2014; Rawson et al., 2011; Tanzila Sultana et al., 2021). Ahmed et al.…”
Section: Influence Of Processing Techniquesmentioning
confidence: 99%
“…Notably, many researchers have forced on the inactivating microorganisms and endogenous enzymes for the purpose of fruit food preservation and conservation (Landl et al., 2010; Liu, Grauwet et al., 2014; Rawson et al., 2011; Tanzila Sultana et al., 2021). Ahmed et al.…”
Section: Influence Of Processing Techniquesmentioning
confidence: 99%
“…9 Other studies have also shown that irradiation can improve the quality of fruits and vegetables such as pineapple, 10 grapes, 11 broccoli, and strawberry after harvest, 12 demonstrating that it is a safe and effective way to reduce the risk of foodborne illnesses and extend the shelf life of food products. 13 Among these irradiation sources, research has shown that 60…”
Section: Introductionmentioning
confidence: 99%
“…Food sterilization through irradiation has been practiced since 1956, when Dr. Charles Artandi (Ethion Inc.) pioneered the process . Sultana et al explored the potential of irradiation to extend the shelf life of mangoes, finding that exposing the fruit to γ-rays, X-rays, or electron beams could increase its shelf life, delay ripening, and prevent the growth of microorganisms and insect infestations. Kalaiselvan et al discovered that irradiation has minimal impact on the flavor, color, taste, and nutritional value of food .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation